Design, Synthesis and Evaluation of 2,4,6-substituted Pyrimidine Derivatives as BACE-1 Inhibitor: Plausible Lead for Alzheimer’s Disease - Jain, Priti; Wadhwa, Pankaj K.; Jadhav, Hemant R. (Medicinal Chemistry, 2021)
Alzheimer’s disease is one of the most common neurodegenerative disorder afflicting a large mass of population. BACE-1 (β-secretase) is an aspartyl protease of the amyloidogenic pathway considered responsible for Alzheimer’s disease (AD). Since it catalyzes the rate-limiting step of Aβ-42 production from amyloid precursor protein (APP), its inhibition is considered a viable therapeutic strategy. We have reported the design of small molecular weight compounds supposed to be blood brain permeable as BACE-1 inhibitors. The clue for the design of this series is drawn from the previously designed series from our research group. Objective: Design and synthesis of 2,4,6-substituted pyrimidine derivatives has been reported. In vitro FRET-based screening of synthesized derivatives was performed to evaluate the BACE-1 inhibition profile. Methods: Based on the docking simulation studies, a library of derivatives was designed, synthesized and evaluated for BACE-1 inhibition in-vitro. The docking studies were performed on Glide (Schrodinger suite) and Molegro virtual docker. Theoretical toxicity was predicted using Osiris Property Explorer. The synthesized compounds were tested for BACE-1 inhibition using in vitro assay based on Fluorescence Resonance Energy Transfer technique. The percent inhibition was calculated as a measure of activity. Results: The designed compounds revealed strong interactions with the desired amino acids of BACE-1 active sites. The aromatic rings placed at the fourth and sixth position of the pyrimidine ring occupied S1 and S3 substrate-binding clefts while the amino group formed hydrogen bonding interactions with Asp32 and Asp228. In silico data ensured that the compounds were orally bioavailable and brain permeable. The in vitro testing showed that the compounds inhibited BACE-1 at 10μM concentration. Conclusion: Compounds substituted with m-benzyloxy on one aromatic ring and o,p-di-chloro on another aromatic ring displayed maximum BACE-1 inhibition. Compound 2.13A displayed high docking score and was found to be most potent with IC50 of 6.92μM. The series displayed a good correlation between the docking score and BACE-1 inhibition profile.
Keywords: Claisen-Schmidt reaction